Penentuan Pengaruh Jenis Pelarut Pengekstrak Terhadap Perolehan Kadar Senyawa Fenolat Dan Aktifitas Antioksidan Dari Daun Jambu Biji (Psidium guajava L.) - Harrizul Rivai; Rizky Yulion Putra; Krisyanella Krisyanella (STIFARM Padang, 2012)
Influence of type of extracting solvent on determination of phenolic compound level and antioxidant activities of Guava Leaf (Psidium Guajava, L.) have been done. The determination of phenolic compound by using Folin-Ciocalteau method and Antioxidant activities by using DPPH method that Gallic Acid was used as reference and determination of phenolic compound and antioxidant activities by using UV-Visible spectrophotometry. The content of phenolic compound from methanol:water extract; ethanol:water extract; aceton:water extract are 82.2699; 81.4762 and 80.9206 mg/g respectively. The finding showed that methanol: water solvent is the best solvent for Phenolat extract compare with ethanol:water and aceton:water. Antioxidant activities from methanol:water extract: ethanol:water ; aceton:water are IC50 3.694; 8.249 and 4.968 mg/mL respectively. From the data can get conclusion that methanol:water is the best solvent for extracting Guava Leaf (Psidium Guajava, L.).